2022
DOI: 10.3390/nano12173040
|View full text |Cite
|
Sign up to set email alerts
|

Manufacturing of Zinc Oxide Nanoparticle (ZnO NP)-Loaded Polyvinyl Alcohol (PVA) Nanostructured Mats Using Ginger Extract for Tissue Engineering Applications

Abstract: In this research, as an alternative to chemical and physical methods, environmentally and cost-effective antimicrobial zinc oxide nanoparticles (ZnO NP) were produced by the green synthesis method. The current study focuses on the production of ZnO NP starting from adequate precursor and Zingiber officinale aqueous root extracts (ginger). The produced ZnO NP was loaded into electrospun nanofibers at different concentrations for various tissue engineering applications such as wound dressings. The produced ZnO N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Ag NPs of thyme extract showed no cytotoxic activity less than the concentration of 3.5 ppm. Izgis et al [54] conducted a study to evaluate the survivability of cells on polyvinyl alcohol (PVA)-based patches loaded with green-synthesized ZnO NPs at concentrations of 20%, 40%, and 60%, as well as on pure PVA electrospun patches. The MTT test was employed to assess cell viability in this investigation.…”
Section: Mtt-based Cytotoxicitymentioning
confidence: 99%
“…Ag NPs of thyme extract showed no cytotoxic activity less than the concentration of 3.5 ppm. Izgis et al [54] conducted a study to evaluate the survivability of cells on polyvinyl alcohol (PVA)-based patches loaded with green-synthesized ZnO NPs at concentrations of 20%, 40%, and 60%, as well as on pure PVA electrospun patches. The MTT test was employed to assess cell viability in this investigation.…”
Section: Mtt-based Cytotoxicitymentioning
confidence: 99%
“…26 In this study, biocompatible and biodegradable poly(vinyl alcohol) (PVA) has been reported in the literature to promote oxygen permeability, which can be a crucial feature for corneal tissue engineering field. 27,28 On the other hand, due to its excellent transparency, gelatin (GEL) has been used in ocular tissue engineering. 29 In this study, PVA/GEL nanofibers enriched with cinnamaldehyde and gentamicin were produced with an electrospinning method aiming to develop an alternative method for bacterial keratitis treatment by designing nanofibrous layers that inhibit biofilm formation and could serve as a corneal patch.…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is a simple, versatile nanofiber production method that allows the production of biomimetic scaffolds from natural and synthetic polymers, consisting of a large network of interconnected fibers and pores, allowing the proficient exchange of nutrients and metabolic wastes, thanks to its high porosity . In this study, biocompatible and biodegradable poly­(vinyl alcohol) (PVA) has been reported in the literature to promote oxygen permeability, which can be a crucial feature for corneal tissue engineering field. , On the other hand, due to its excellent transparency, gelatin (GEL) has been used in ocular tissue engineering …”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide nanoparticles (ZnO NPs) are antibacterial materials with superior antibacterial properties to silver nanoparticles by producing reactive oxygen species [ 19 , 20 , 21 ]. Furthermore, the biocompatibility to human gingival fibroblast cells and L929 mouse fibroblast cells of ZnO NPs in dental and medical applications has been confirmed, and ZnO NPs have been used in composite resins, endodontic sealers, and adhesive cements in dental fields [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%